Remodelación del Laboratorio de Microbiología Clínica del INER para el cumplimiento de estándares de bioseguridad - Pimentel-Aguilar, A. B.; Rodríguez Vera, R. N.; Méndez Salinas, C. L. (Revista Mexicana de Ingenieria Biomedica, 2007)
The infection risk by Mycobacterium tuberculosis is high for the microbiology laboratory personal. It is possible to handle this bacterium using the proper engineering adjustments, administrative procedures and personal working with the appropriate safety measures to content the organism and to ensure the staff protection to that exposition. The Clinical Microbiology Laboratory of the National Institute of Respiratory Diseases deals with tuberculosis multi-drug resistant. An evaluation of the biosafety norms application in that clinical area showed facilities biosafety deficiencies. The purpose of this work was to propose a modification of the Laboratory, determining the actual biosafety level and, according to it, defining the facilities and equipment characteristics required to create a safe environment for the person; the qualitative benefits of the modifications are also presented. A cost-utility analysis demonstrated that the project monetary inversion is equivalent to thirteen years of treatment of common tuberculosis infected person, or three years in the case of multi-drug resistant tuberculosis infection.